Factors Affecting Fishermen’s Income in Mangkoso Village, Soppeng Riaja District, Barru Regency - Dewi, Andi Kumala Sari; Rusydi, Muhammad; Naidah (AKSIOMA : Jurnal Manajemen, 2025)
The objective of this research is to examine the underlying elements that shape the earnings of coastal fishers in Mangkoso Village, located within Soppeng Riaja Subdistrict, Barru Regency. The study adopts a quantitative methodology, with information gathered through structured surveys and archival records. Both firsthand observations and existing materials served as the data foundation, while the instrument applied was a Likert-type scale. The processing and interpretation of the data were facilitated using the SPSS statistical program. The outcomes indicate that financial capital exerts a downward yet non-substantial effect on fishers’ earnings. On the other hand, commodity prices and environmental shifts demonstrate a positive and meaningful contribution to income levels. Consequently, strategies focusing on market conditions and ecological variability are essential to maintain the financial resilience of fishing communities in the region.